InCoDe 2008 - Impediments and Resolutions to Innovation in a Chinese Food Manufacturer: The Case Study - Hong, Woo S. (Marketing & Menedzsment, 2019)
The food industry is a major industry in China consisting of both local Chinese owned and managed firms, and foreign ventures, often operating in competitive environments. This paper examines the case of a family owned Chinese food manufacturer in Beijing. The need to innovate is clear from the challenges faced by the firm such as changing consumer preferences; and competition from local and foreign firms. This paper finds that impediments to innovate include a deep rooted inward favouring tradition; a reliance on the use of experience rather than on analytical techniques; a hierarchical and controlling management structure and style that discourage deviations from established practices; and low absorptive capacity. The resolutions include adjusting the firm’s organisational structure and management style; introducing more qualified and innovative favouring staffs; formalising research and development; and implementing structured and formal training.